Knowledge, Attitude and Practice of Personal Hygiene among Grade Nine and Ten Students in Government School of Jumla - Neupane, Pratima; Panta, Prem Prasad; K.C, Shreejana; Padhaya, Ramesh Raj; Bhattarai, Preeti; Lama, Nishant (Journal of Nepal Health Research Council, 2024)
Background: Personal hygiene is crucial for a healthy life, especially for school children who are more susceptible to diseases due to poor hygiene. This study was design to determine the existing knowledge, attitude and practice of personal hygiene among secondary students of grade nine and ten of a government school of Jumla. Methods: A school-based cross-sectional study was conducted in a Government Secondary school situated in a rural area of Jumla. A total of 368 adolescent girls and boys from classes nine and ten were included. Data were collected using pre-tested, self-administered questionnaires and analyzed with SPSS version 16. The Chi-square test was applied to compare the proportions of quantitative variables.Results: Among the 368 students, 43.3% were male and 52.7% were female, with a mean age of 14.98 Â± 1.34 years. The study found that 94.8% had good knowledge, 82.3% had a positive attitude towards personal hygiene, and 63.6% practiced good personal hygiene. Participants with a positive attitude towards personal hygiene demonstrated a higher percentage of good hygiene practices. However, there was no statistically significant association between knowledge and attitude on personal hygiene. Conclusions: The study revealed that the majority of the students had a good level of personal hygiene knowledge. Boys appeared to be more knowledgeable than the girls; though these knowledge and attitude were not reflected in their practices. The study proposed that health education should focus on enhancing the attitude and practice to improve hygiene among rural youth.Keywords: Attitude; knowledge; personal hygiene; practices; rural government school.